The efficacy of Dexamethasone in the prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy - Adra, Lama; Ibrahim, Tyseer; ALaji, Bahaa (Latakia University Journal -Medical Sciences Series, 2018)
This study was carried out in the department of anesthesia at Tishreen university hospital , Lattakia , Syria , during the year 2016-2017 . A total of 120 patients , aged between 30 and 50 years old , posted for elective laparoscopic cholecystectomy under general anesthesia belonging to the American society of Anesthesiologist (ASA) physical status ǀ-ǀǀ were included in the study . Patients were divided into three groups : patients in the first group received 2 ml normal saline ( group A ) . Patients in the second group D1 received 8 mg Dexamethasone preoperatively . Patients in the third group D2 received 8 mg immediately after removing the gallbladder from her place. The gall of the study was to show the efficacy of Dexamethasone in the prevention of postoperative nausea and vomiting . the result was better in the second group and the conclusion is that Dexamethasone is effective in prevention of PONV and it is better when we use dexamethasone preoperatively . فعالية الديكساميتازون في الوقاية من الغثيان والإقياء في فترة ما بعد جراحة استئصال المرارة بالتنظير أجريت هذه الدراسة في قسم التخدير و الإنعاش في مشفى تشرين الجامعي في اللاذقية خلال العامين 2016-2017 . تضمنت هذه الدراسة 120 مريض أجري لهم استئصال مرارة بالتنظير تحت التخدير العام وينتمون إلى تصنيف الجمعية الأمريكية للتخدير ASA ǀ-ǀǀ . قسم المرضى إلى ثلاثة مجموعات : المجموعة الأولى أعطيوا 2 مل سيروم مالح سوي التوتر (المجموعة A ) ، المرضى في المجموعة الثانية D1 أعطيوا 8 ملغ ديكساميتازون كتحضير دوائي . المرضى في المجموعة الثالثة D2 أعطيوا 8 ملغ ديكساميتازون بعد تسليخ المرارة من كامل مسكنها . هدف البحث هو لإظهار فعالية الديكساميتازون في الوقاية من الغثيان و الإقياء بعد العمل الجراحي . كانت النتائج أفضل في المجموعة الثانية ، والخلاصة هي أن الديكساميتازون فعال في الوقاية من الغثيان و الإقياء بعد العمل الجراحي و من الأفضل إعطاءه كتحضير دوائي .